Correlation between peripheral venous and arterial blood gas measurements in patients admitted to the intensive care unit: A single-center study - Bo Ra Kim; Sae Jin Park; Ho Sik Shin; Yeon Soon Jung; Hark Rim (The Korean Society of Nephrology, 2013)
Background: The objective of this study was to examine the correlation between arterial blood gas (ABG) and peripheral venous blood gas (VBG) samples for all commonly used parameters in patients admitted to a medical intensive care unit (ICU). Methods: A single-center, prospective trial was carried out in a medical ICU in order to determine the level of correlation of ABG and peripheral VBG measurements. A maximum of five paired ABG-VBG samples were obtained per patient to prevent a single patient from dominating the data set. Results: Regression equations were derived to predict arterial values from venous values as follows: arterial pH=−1.108+1.145×venous pH+0.008×PCO2−0.012×venous HCO3+0.002×venous total CO2 (R2=0.655), arterial PCO2=88.6−10.888×venous pH+0.150×PCO2+0.812×venous HCO3+0.124×venous total CO2 (R2=0.609), arterial HCO3=−89.266+12.677×venous pH+0.042×PCO2+0.675×venous HCO3+0.185×venous total CO2 (R2=0.782). The mean ABG minus peripheral VBG differences for pH, PCO2, and bicarbonates were not clinically important for between-person heterogeneity. Conclusion: Peripheral venous pH, PCO2, bicarbonates, and total CO2 may be used as alternatives to their arterial equivalents in many clinical contexts encountered in the ICU.